2009
DOI: 10.1111/j.1600-0404.2009.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Boron Neutron Capture Therapy for glioblastoma multiforme: advantage of prolonged infusion of BPA-f

Abstract: Prolonged infusion was found to be beneficial for the efficacy of BNCT and it is suggested that 6 h infusion of BPA-f should be used in future trials of BNCT for GBM. BNCT, which is a single-day treatment with mild side effects, should be assessed in a controlled trial, as an alternative to 30 daily fractions of conventional fractionated photon therapy over a period of 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Kaplan-Meier plots comparing the survival for all patients from the two arms of the randomised trial by Stupp et al [4] with the Studsvik BNCT study [8,9] are shown in Figure 1a,b. A similar analysis for RPA Class V patients alone [3] is given in Figure 1c,d.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kaplan-Meier plots comparing the survival for all patients from the two arms of the randomised trial by Stupp et al [4] with the Studsvik BNCT study [8,9] are shown in Figure 1a,b. A similar analysis for RPA Class V patients alone [3] is given in Figure 1c,d.…”
Section: Resultsmentioning
confidence: 99%
“…The patient characteristics and medical interventions in the two arms of the trial as published by Mirimanoff et al [3] and as published in the BNCT study [9] are given in Table 1. The median age of the patients in the BNCT study was slightly lower, and the fraction of patients with initial surgery was slightly higher, than indicated by Mirimanoff et al [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that trial the MST was 10.4-13.2 months for newly diagnosed GBM patients. In a Swedish clinical trial 29 newly diagnosed GBM patients received an infusion of 900 mg/kg BPA in the course of 6 hours (22)(23)(24)(25). The MST was 17.7 months compared to 15.5 months in patients who received standard therapy comprised of surgery followed by RT and TMZ.…”
Section: Discussionmentioning
confidence: 99%